Oncología pediátrica - Pacheco, Mónica; Madero, Luis (Psicooncología, 2003)
Cancer in chilhood is becoming increasingly important in the field of Pediatrics; among other reasons as it the second cause of infant mortality. The possibility of detecting genetic and molecular alterations in tumoral cells can allow the patient´s risk to be individualized and, as a consequence, treatments which are just as effective but less toxic to be used. Although over recent years we have seen a spectacular advance in the survival of cancer in chilhood and few specialties have attained similar results, it is probably that a new era in research on and treatment of tumors in the infant has begun.
Keywords: Cancer; Tumors in the infant